THE PRIZE OF DEATH: Understanding the Phenomenon of ‘Suicide Attacks’ or ‘Martyrdom Operations’ in Modern Radical Islam - M. Byrne, Dermot (Asian Horizons, 2017)
The increasingly prevalent phenomenon of suicide attacks by radical Islamists in Europe and elsewhere has led to confusion and uncertainty among the non-Muslim and Muslim population regarding the cause and legitimacy of such actions within Islam. While the practice is condemned by Muslims and others, many are left perplexed as to the root cause of the practice and why it seems to be more common in Islam than in other religions. The aims of this article are to try and understand the genesis and development of the phenomenon, and to elucidate the arguments in support of suicide attacks. In order to do so there will be a diachronic study of Islamic martyrologies from the time of the life of Muhammed and more modern conceptions. There will also be an examination of the manner in which theologies of Jihad inform attitudes to martyrdom. In an era of increased religious polarisation a greater understanding of the factors influencing both ourselves and the religious other are of increasing importance.